From Student to Teacher: Medical Student Perceptions of Teaching Children and a Novel Application of the One Minute Preceptor - Laura Cline; Muna Canales (University Library System, University of Pittsburgh, 2020)
Background: As students progress through medical school, the student assumes teaching roles, but without formal training regarding how to teach. Methods: We administered surveys to 1st, 2nd and 4th year medical students asking about perceptions of teaching. The surveys were completed in the Fall (2019) and again in late Spring (2020). In the interim, students were given the opportunity to teach 5th graders during an outreach program. We gave the medical student volunteers a brief interactive session about the One Minute Preceptor (OMP) as a tool to teach the children. In the Spring survey, medical students who used the OMP were also asked about its utility in the pediatric setting. Results: Seventy-four students completed survey 1 and, of these, 51 completed the follow-up survey. Mean age was 24-27; 57% were female. Across both surveys, ?70% were comfortable with and felt they understood their role as a teacher of trainees, peers, and patients. However, <50% felt they knew any teaching method or had a plan for improving teaching skills. All felt that teaching was an important medical skill. Six students completed OMP training and the outreach program. All felt the OMP was useful to teach key points, provide feedback, and involve the learner. They also all felt the OMP should be taught in medical school. Conclusion: Medical students believe it is important to learn teaching skills. The OMP may be a useful addition to the medical school curriculum to help medical students teach in doctor-patient settings across ages and group sizes.